Quality of life, burden, family emotional support: a model for older adults who are caregivers - Carola Rosas; Anita Liberalesso Neri (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To investigate associations between quality of life, sex, age, burden, and nature of emotional support available in the family in older adults who are caregivers of older relatives. Method: Cross-sectional and correlational study on 148 caregivers gathered in public and private healthcare services, who were subjected to psychological measures of quality of life, burden, exchange of emotional support, sex, and age. Data were analyzed using Chi-square, Fisher's exact test and path analyses (p < 0.05). Results: A total of 77% women, average age of 69.7 years. There were significant associations between exchange of support and burden due to the provided assistance, being a woman and satisfaction with the received support, satisfaction with the received support and burden, burden and quality of life, and satisfaction with the received support and feeling of burden due to the provided support. Conclusion: Satisfaction with the received emotional support moderate the association between sex and burden, and such moderate the association between satisfaction with emotional support and perceived quality of life.